THE EFFECTIVENESS OF THE CLT APPROACH IN ENHANCING SPEAKING SKILLS IN YOUNG ESL LEARNERS - Musoyeva Aziza Botirovna,; Mirjalolova Maftunaxon Omonjon qizi,; Nosirova Moxlaroy Maksudjon qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This theoretical article examines the effectiveness of Communicative Language Teaching (CLT) in enhancing speaking skills among young English as a Second Language (ESL) learners. Through a comprehensive review of existing literature and theoretical frameworks, the study analyzes how CLT principles facilitate oral language development in children. The methodology involves systematic analysis of CLT implementation strategies, pedagogical approaches, and theoretical foundations that support speaking skill acquisition. Results indicate that CLT's emphasis on meaningful interaction, fluency over accuracy, and learner-centered activities creates optimal conditions for young learners to develop communicative competence.